2013
DOI: 10.1590/s0100-204x2013000700004
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de feijão‑caupi e milho semeados em faixas na safrinha

Abstract: Resumo -O objetivo deste trabalho foi avaliar o desempenho agronômico de cultivares de feijão-caupi e de milho, em monocultivo e em cultivo consorciado em faixas, na safrinha. Foram realizados experimentos, em Dourados, MS (2009 e 2010, e em Botucatu, SP (2010). Utilizou-se o delineamento experimental de blocos ao acaso, com parcelas subdivididas e quatro repetições. As parcelas com feijão-caupi foram constituídas por três sistemas de cultivo (em faixas com variedade ou híbrido de milho, além do cultivo soltei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
2
1
3
Order By: Relevance
“…Although the significant effect found for the variable number of grains per pod (Figure 6) does not seem to be so marked, the increase of 1.2 grains per pod, obtained with the highest dose in this study, represents an increase of 9.5%, when compared to plants without the addition of P. Considering that the number of pods per plant and number of grains per pod are the factors that most influence productivity, the increase achieved with the application of P doses should be carefully evaluated. Working with different cowpea cultivars, Matoso et al (2013), found a greater number of grains per pod for the same cultivars in this study, however, the authors attributed this yield to genetic heritability, reporting little influence from their treatments.…”
Section: Resultscontrasting
confidence: 60%
“…Although the significant effect found for the variable number of grains per pod (Figure 6) does not seem to be so marked, the increase of 1.2 grains per pod, obtained with the highest dose in this study, represents an increase of 9.5%, when compared to plants without the addition of P. Considering that the number of pods per plant and number of grains per pod are the factors that most influence productivity, the increase achieved with the application of P doses should be carefully evaluated. Working with different cowpea cultivars, Matoso et al (2013), found a greater number of grains per pod for the same cultivars in this study, however, the authors attributed this yield to genetic heritability, reporting little influence from their treatments.…”
Section: Resultscontrasting
confidence: 60%
“…The second, or fall-winter, crop in the central-west and southeast regions of Brazil is characterized by a sowing time between January and March, with a predominance of corn (Zea mays L.), as a consequence of the few economically viable alternatives for that period (Matoso et al, 2018;Shioga, Oliveira, & Gerage, 2004). However, the fall-winter crop options have been more susceptible to yield losses mainly resulting from water stress in later sowing, potentially causing yield reductions ranging from 80 to 100% in some years (Matoso, Soratto, Ceccon, Figueiredo, & Neto-Neto, 2013, Matoso et al, 2018Pegorare, Fedatto, Pereira, Souza, & Fietz, 2009). Therefore, because of its relative tolerance to water deficiency, short cycle, adaptation to less fertile soils, and low production costs, in addition to the increased demand for this legume by the domestic and foreign markets, cowpea has been emerging as an interesting option for farmers as a second crop (Matoso et al, 2013(Matoso et al, , 2018Olajide & Ilori, 2016;Oliveira, Andrade-Júnior, Ribeiro, Brito, & Carvalho, 2015;Timko & Singh, 2008).…”
Section: Crop Sciencementioning
confidence: 99%
“…Several studies present lower grain yields to those found in Janaúba. This is found for the cultivars BRS-Xiquexique (MATOSO et al, 2013), BRS-Cauame (SANTOS et al, 2016), BRS-Marataoa (SILVA; NEVES, 2011), and BRS-Pajeu (LOCATELLI et al, 2014).…”
Section: Resultsmentioning
confidence: 81%